The Consequences Of The Law Caused By The Division Of Gono-Gini Property In The Gorontalo Religious Court - Dwi Marcelia Hasan (Estudiante Law Journal, 2019)
The type of research used by researchers in the preparation of scientific articles is a type of normative legal research with juridical sociological research methods that have objects of study of behavior in society. The termination of marriage will inevitably have legal consequences, for example, marriage between a man and a woman is a legal relationship that gives rights and obligations to both parties. Legal consequences are also interpreted as the consequences given by law for an action of a legal subject. Not only will a marriage have legal consequences, but the termination of the marriage will also have legal consequences either the termination of the marriage due to death or a court ruling.Keywords: Legal Consequences, Division, Gono-Gini Treasures